Taxonomic and nomenclatural notes on Boerhavia (Nyctaginaceae) in India - Ravichandran, Arun Prasanth; Sardesai, Milind M.; Yadav, S. R. (Phytotaxa, 2020)
Boerhavia coccinea (Nyctaginaceae) is recorded for the first time in India (Satara district, Maharashtra). The name B. procumbens, previously synonymized with B. diffusa, is here accepted for a distinguished species on the basis of nature of stem (color and hairiness), hairs on leaf margin, type of inflorescence and shape of the anthocarp. The current distribution of B. procumbens in India is also provided. A detailed description, as well as illustration, photographs, distribution and a morphological comparison among B. coccinea, B. crispa, B. procumbens, and B. diffusa are also given. Lectotypes of the names B. crispa and B. procumbens (deposited at K) are designated.